Mechanism based nonlinear constitutive model for composite laminates subjected to large deformations. (15th November 2015) - Mandel, Ulrich; Taubert, Robin; Hinterhölzl, Roland
Abstract: A nonlinear constitutive model for composite laminates is developed with the focus on the distinction among inducing mechanisms. It is shown, that the effect of fiber rotation and damage is essential in consideration of large deformations. The evolution of yielding is described by two independent hardening curves either for in-plane shear or transverse normal load. A method for the experimental determination of the hardening curves is proposed based on uniaxial tests. To ensure the applicability to structural parts, the numerical model is validated by a large number of various angle-ply tension and off-axis compression tests, fabricated of the same carbon/epoxy IM7-8552 material. Extra wide specimen geometry was used for the conducted angle-ply tension tests to prevent delamination failure. The implemented model shows excellent correlation even at very large shear strains of up to 14%.